Pengaruh Brand Engagement terhadap Brand Loyalty Dimediasi oleh Brand Trust dan Brand Experience - Prestyse Desputri Gulo; Andri Kusmayadi (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
Increasing competition in the digital streaming service industry has prompted companies to build long-term relationships with consumers, one of which is through increased Brand Engagement. This study aims to determine the effect of Brand Engagement on Brand Loyalty with Brand Trust and Brand Experience as mediating variables. The study employs a quantitative approach through an online survey of 160 Netflix users aged 17–28 years in Jakarta, selected using purposive sampling, with data analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that Brand Engagement positively influences Brand Trust, Brand Experience, and Brand Loyalty, with Brand Trust and Brand Experience acting as mediators in this relationship. These findings confirm that high consumer engagement can create positive experiences and trust in the brand, which ultimately leads to loyalty. For future research, it is recommended to expand the scope of respondents with more diverse regional and age variations, as well as consider external variables such as subscription prices, network quality, and competitor influence. The managerial implications of this study suggest that digital service companies like Netflix need to strengthen consumer engagement both emotionally and functionally through the development of interactive features, consistent service, and quick responses to complaints, so that positive experiences and consumer trust can be maintained and ultimately lead to loyalty.